Phase boundary coherent refractory alloy and preparation method and application thereof
Through gel-combustion method and discharge plasma sintering technology, a phase boundary co-united alloy is prepared, which solves the problem of coupling densification and grain growth, and realizes a high-density and ultra-fine grain refractory alloy, which improves the room temperature and high-temperature mechanical properties of the material.
Patent Information
- Application Number
- CN202510090969.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In the prior art, densification and grain growth are coupled during powder metallurgy, resulting in high brittleness at room temperature, limiting its performance and application range.
The gel-combustion method is used to prepare the core-shell structure refractory alloy powder, and the preparation of the phase boundary co-uniform refractory alloy is achieved through two-step sintering technology of discharge plasma. This method eliminates pores while ensuring a small particle size and obtains a high density alloy.
A phase boundary co-fusion alloy with high density and ultrafine grains is achieved at room temperature, which improves the mechanical properties of the material, especially at high temperatures, and can maintain high compression strength.
Smart Images

Figure CN119870486A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy and relates to a phase boundary coherent refractory alloy and a preparation method and application thereof. Background Art
[0002] Metal tungsten (W), metal molybdenum (Mo) and metal rhenium (Re) have a series of excellent properties such as high melting point, high elastic modulus and strength, and low thermal expansion coefficient. They play an important role in modern defense, atomic energy, electric vacuum and other engineering application fields, and play an irreplaceable role in some special high-temperature application fields. Metal tungsten and molybdenum are brittle at room temperature and have a high ductile-brittle transition temperature (DBTT), which not only makes it impossible to deform metal tungsten and molybdenum at room temperature, but also limits the full play of their performance and application scope. Therefore, improving the room temperature brittleness of metal tungsten and molybdenum is crucial to the development of metal tungsten and molybdenum products.
[0003] For refractory alloy materials, heterogeneous interfaces often become the source of crack initiation and material damage due to the incompatibility of stress and strain. The coherent interface can maintain high-strength interface bonding and realize uniform deformation and dislocation propagation, so it plays an important role in ensuring the interface bonding of heterogeneous materials. As typical refractory metals, the preferred preparation strategy for W, Mo and Re is powder metallurgy. However, during the powder sintering process, densification is coupled with grain growth. Due to the low density limitation, the traditional process has to sinter at a temperature above 1800°C, sacrificing the grain size to increase the relative density of the material. Therefore, it is of great significance to effectively control the grain growth of nanopowders, achieve complete densification and obtain excellent interface bonding for the development of refractory alloys.
[0004] Modifiers are a class of chemical substances that can change the performance of materials by regulating the microstructure or surface properties of materials. They can interact with the surface of materials through physical or chemical methods to improve the wettability and adhesion of the material surface. They can improve the dispersibility and anti-caking properties of metal powders, and improve the compatibility and wettability of metal powders in organic polymer materials. Surface modifiers are widely used in fields such as material science, chemical engineering and manufacturing, and can effectively improve the performance and service life of materials. Summary of the invention
[0005] In order to solve the problem of coupling between densification and grain growth in the prior art, the present invention proposes a method for preparing phase-boundary coherent refractory alloys by a gel-combustion method based on the sol-gel method and spark plasma sintering technology. The method first adopts the gel-combustion method to prepare core-shell structured refractory alloy powder, and then uses the spark plasma two-step sintering technology to prepare phase-boundary coherent refractory alloys. The refractory alloy prepared by the method of the present invention can eliminate pores while ensuring a fine particle size, and ultimately obtain a high density.
[0006] The first aspect of the present invention provides a phase boundary coherent refractory alloy, in which the oxide of the second phase high melting point metal forms a coherent phase interface with the refractory metal, and the oxide of the second phase high melting point metal is dispersed in the refractory metal;
[0007] The refractory metal is selected from one of tungsten (W), molybdenum (Mo) or rhenium (Re); the second phase high melting point metal is selected from one of zirconium (Zr), yttrium (Y), aluminum (Al), lutetium (Lu), cerium (Ce), hafnium (Hf), thorium (Th), and lanthanum (La);
[0008] The volume fraction of the oxide of the second phase high melting point metal in the phase boundary coherent refractory alloy is 3%-30%.
[0009] Furthermore, the volume fraction of the oxide of the second phase high melting point metal in the phase boundary coherent refractory alloy is 5.0% to 15.0%.
[0010] Furthermore, the relative density of the phase boundary coherent refractory alloy is not less than 98.0%, and the grain size is less than 1.0 μm;
[0011] Furthermore, the relative density is not less than 98.5%, and the grain size is 0.5 μm-0.8 μm.
[0012] The second aspect of the present invention provides a method for preparing the above-mentioned phase boundary coherent refractory alloy, the preparation method comprising the following steps:
[0013] Step 1, preparing raw materials: using a water-soluble salt of a refractory metal, a water-soluble salt of a second-phase high-melting-point metal, a modifier, ammonium nitrate and glycine as raw materials; wherein the ratio of the water-soluble salt of the refractory metal to the water-soluble salt of the second-phase high-melting-point metal is, based on the sum of the volume of the refractory metal in the water-soluble salt of the refractory metal and the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal being 100%, the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal is 3%-30%; the refractory metal is selected from one of tungsten (W), molybdenum (Mo) or rhenium (Re); the second-phase high-melting-point metal is selected from one of zirconium (Zr), yttrium (Y), aluminum (Al), lutetium (Lu), cerium (Ce), hafnium (Hf), thorium (Th), lanthanum (La); the modifier is a water-soluble small molecule compound or a polymer;
[0014] Step 2, preparing alloy powder: mixing the raw materials and preparing a uniform aqueous solution, and in-situ compounding under heating conditions to form a core-shell complex gel; then heating to 500°C to 700°C to produce a combustion reaction to prepare a coated core-shell precursor powder containing a refractory metal oxide and a second phase high melting point metal oxide; continuing to reduce the coated core-shell precursor powder in a reducing gas at a temperature of 600°C to 1200°C to prepare an alloy powder with a core-shell structure in which a refractory metal is coated with a second phase high melting point metal oxide;
[0015] Step 3, forming and sintering: the alloy powder obtained in step 2 is pressed and formed, and a two-step sintering method of spark plasma is adopted, firstly, the temperature is raised to the pre-sintering temperature by spark plasma sintering method, and the temperature is kept for 1min to 2min, then the temperature is reduced to the densification sintering temperature, and the temperature is kept for 3min to 6min, so as to obtain a phase boundary coherent refractory alloy; wherein the pre-sintering temperature is 1500℃ to 1800℃, and the densification sintering temperature is 120℃ to 350℃ lower than the pre-sintering temperature.
[0016] Furthermore, in step 1, the water-soluble salt of the refractory metal is selected from ammonium metatungstate, sodium tungstate, ammonium tungstate, ammonium molybdate, sodium molybdate, potassium molybdate, ammonium rhenate, sodium rhenate, and potassium rhenate.
[0017] Furthermore, in step 1, the water-soluble salt of the second phase high melting point metal is selected from aluminum nitrate, zirconium nitrate, yttrium nitrate, lutetium nitrate, cerium nitrate, hafnium nitrate, thorium nitrate, lanthanum nitrate, zirconium chloride, yttrium chloride, aluminum chloride, lutetium chloride, cerium chloride, hafnium chloride, thorium chloride, and lanthanum chloride.
[0018] Furthermore, in step 1, based on the sum of the volume of the refractory metal in the water-soluble salt of the refractory metal and the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal being 100%, the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal is 5.0% to 15.0%.
[0019] Furthermore, in step 1, the modifier is selected from one of stearic acid (SA), polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB), and sodium dodecyl sulfate (SDS).
[0020] Furthermore, in step 1, the amount of the modifier added is 0.1% to 0.5% of the mass of the refractory metal in the water-soluble salt of the refractory metal, preferably in the range of 0.15% to 0.25%.
[0021] Furthermore, in step 1, the molar ratio of the water-soluble salt of the refractory metal, ammonium nitrate and glycine is 1:1.3-2.6:3-6; preferably, the molar ratio of ammonium nitrate to glycine is 1:1.4-2.5:3.2-5.4.
[0022] Furthermore, in step 2, the temperature used for in-situ composite formation of the core-shell complex gel under heating conditions is 150°C-300°C.
[0023] Furthermore, in step 2, the solvent in the aqueous solution is evaporated and concentrated under heating conditions to obtain an in-situ composite core-shell complex gel.
[0024] Furthermore, in step 2, the temperature of the combustion reaction is preferably 500°C-650°C.
[0025] Furthermore, in step 2, the reduction temperature range is 700°C to 800°C.
[0026] Furthermore, in step 2, the reducing gas is hydrogen.
[0027] Furthermore, in step 2, the average particle size of the obtained alloy powder is less than 50 nm, preferably 20 nm-40 nm.
[0028] Furthermore, in step 3, the pre-sintering temperature is 1550° C. to 1650° C., and the holding time is 1 min to 2 min.
[0029] Furthermore, in step 3, the densification sintering temperature is 150° C. to 300° C. lower than the pre-sintering temperature, and is kept warm for 4 to 5 minutes.
[0030] Furthermore, the relative density of the phase boundary coherent refractory alloy is not less than 98.0%, and the grain size is less than 1.0 μm; further, the relative density is not less than 98.5%, and the grain size is 0.5 μm-0.8 μm.
[0031] A third aspect of the present invention provides a phase boundary coherent refractory alloy prepared by the above preparation method.
[0032] A fourth aspect of the present invention provides the use of the above-mentioned phase boundary coherent refractory alloy as a material for turbine blades and combustion chambers.
[0033] Beneficial Effects
[0034] 1. The process for preparing alloy powder of the present invention is simple and fast, and can realize one-step synthesis of alloy powder without subsequent calcination process. The controllable synthesis of alloy powder core-shell structure is realized, and the alloy powder has fine particle size, and can be powdered in large quantities at the same time, which greatly shortens the preparation time of alloy powder.
[0035] 2. The introduction of modifiers can effectively improve the dispersion state of raw material molecules and ions in solution, promote the formation of a gel with a coating complex structure, and the highly homogenized gel formed can better achieve the elemental uniformity of the precursor and the reduced powder, thereby achieving the dispersed distribution of the second phase oxide of the high melting point metal in the refractory metal.
[0036] 3. The use of pressure sintering technology can effectively improve the density of the sintered body. The spark plasma sintering technology has a fast heating speed and a short sintering time, which can effectively prevent excessive growth of grains and shorten the sintering cycle.
[0037] 4. The two-step sintering process can use the difference in grain boundary diffusion and grain boundary migration dynamics to inhibit grain growth. This method can not only reduce the sintering densification temperature, but also effectively prevent the non-uniform growth of grains, reduce porosity and improve density.
[0038] 5. The oxide of the second phase high melting point metal in the phase boundary coherent refractory alloy provided by the present invention forms a coherent phase interface with the refractory metal, and the second phase oxide of the high melting point metal is dispersed in the refractory metal. The alloy has high-density ultrafine grain characteristics, with a density greater than 98.0%, a grain size not exceeding 1 μm, and a high-temperature compressive strength of more than 1000 MPa at 600°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0040] Figure 1 TEM image of the nano-alumina coherent reinforced tungsten alloy prepared in Example 1 of the present invention, showing the dispersed distribution of alumina in the tungsten matrix.
[0041] Figure 2 1 is a HRTEM photograph of the nano-alumina coherent reinforced tungsten alloy prepared in Example 1 of the present invention, showing the coherent interface formed by the alumina and the tungsten matrix.
[0042] Figure 3 This is a TEM picture of an alumina reinforced tungsten alloy prepared without using the method provided by the present invention, and the second phase particles appear as huge agglomerates.
[0043] Figure 4 This is a HRTEM picture of an aluminum oxide reinforced tungsten alloy that is not prepared using the method provided by the present invention. It is difficult for the two to form a coherent interface. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are described in detail below, but it should not be understood as limiting the applicable scope of the present invention.
[0045] Example 1
[0046] Step 1: Prepare raw materials: take ammonium metatungstate, aluminum nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the ratio of ammonium metatungstate and aluminum nitrate, so that the total volume of aluminum oxide generated by the metal tungsten in the ammonium metatungstate and the aluminum in the aluminum nitrate is 100%, and the volume of aluminum oxide generated by the aluminum in the aluminum nitrate is 15.0%; the ratio of ammonium metatungstate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:1.5:3.2, and the amount of stearic acid is 0.2% of the mass of the metal tungsten in the ammonium metatungstate.
[0047] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, evaporate the solution, concentrate it to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 750°C to obtain a tungsten-coated nano-alumina core-shell alloy powder with a powder size of 27nm.
[0048] Step 3: Forming and sintering: The tungsten-coated nano-alumina core-shell alloy powder obtained in step 2 is pressed to form a formed body, and the formed body is pre-sintered by spark plasma in a vacuum at a pre-sintering temperature of 1600°C for 1 minute, and then cooled to a densification sintering temperature of 1400°C for 5 minutes to prepare a nano-alumina coherent reinforced tungsten alloy.
[0049] The relative density of the obtained nano-alumina coherent reinforced tungsten alloy is 99.7%, the average grain size is 0.5 μm, and the compressive strength at 600°C exceeds 1000 MPa.
[0050] Example 2
[0051] Step 1: Prepare raw materials: take ammonium metatungstate, zirconium nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the ratio of ammonium metatungstate and zirconium nitrate, so that the total volume of zirconium oxide generated by metal tungsten in ammonium metatungstate and zirconium in zirconium nitrate is 100%, and the volume of zirconium oxide generated by zirconium in zirconium nitrate accounts for 5.0% of the total volume; the ratio of ammonium metatungstate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:1.7:3.2, and the ratio of stearic acid is calculated according to 0.2% of the mass of metal tungsten in ammonium metatungstate.
[0052] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, volatilize and concentrate the solution to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 700°C to obtain a tungsten-coated nano-zirconia core-shell alloy powder with a powder size of 33nm.
[0053] Step 3: Forming and sintering: After pressing and forming, the formed body is pre-sintered by spark plasma in vacuum, the pre-sintering temperature is 1550℃, the holding time is 1min, and then the temperature is lowered to the densification sintering temperature of 1250℃ and the holding time is 5min, and the nano-zirconia coherent reinforced tungsten alloy can be prepared. The relative density is 98.9%, the average grain size is 0.7μm, and the compressive strength at 600℃ exceeds 1000MPa.
[0054] Example 3
[0055] Step 1: Prepare raw materials: take ammonium molybdate, lanthanum nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the ratio of ammonium molybdate and lanthanum nitrate, so that the total volume of lanthanum oxide generated by metal molybdenum in ammonium molybdate and lanthanum in lanthanum nitrate is 100%, and the volume of lanthanum oxide generated by lanthanum in lanthanum nitrate accounts for 10.0% of the total volume; the ratio of ammonium molybdate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:1.4:3.3, and the ratio of stearic acid is calculated according to 0.2% of the mass of metal molybdenum in ammonium molybdate.
[0056] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, evaporate the solution, concentrate it to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 800°C to obtain a molybdenum-coated nano-lanthanum oxide core-shell alloy powder with a powder size of 31nm.
[0057] Step 3: Forming and sintering: After pressing and forming, the formed body is pre-sintered by spark plasma in vacuum, the pre-sintering temperature is 1650℃, the holding time is 1min, and then the temperature is lowered to the densification sintering temperature of 1400℃ and the holding time is 5min, and the nano-lanthanum oxide coherent reinforced molybdenum alloy can be prepared. The relative density is 99.2%, the average grain size is 0.6μm, and the compressive strength at 600℃ exceeds 1000MPa.
[0058] Example 4
[0059] Step 1: Prepare raw materials: take ammonium rhenate, yttrium nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the ratio of ammonium rhenate and yttrium nitrate, so that the total volume of yttrium oxide generated by metal rhenium in ammonium rhenate and yttrium in yttrium nitrate is 100%, and the volume of yttrium oxide generated by yttrium in yttrium nitrate accounts for 10.0% of the total volume; the ratio of ammonium rhenate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:2.5:5.4, and the ratio of stearic acid is calculated according to 0.2% of the mass of metal rhenium in ammonium rhenate.
[0060] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, volatilize and concentrate the solution to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 800°C to obtain a rhenium-coated nano-yttrium oxide core-shell alloy powder with a powder size of 35nm.
[0061] Step 3: Forming and sintering: After pressing and forming, the formed body is pre-sintered by spark plasma in vacuum, the pre-sintering temperature is 1670℃, the holding time is 1min, and then the temperature is lowered to the densification sintering temperature of 1450℃ and the holding time is 5min, and the nano-yttrium oxide coherent reinforced rhenium alloy can be prepared. The relative density is 98.9%, the average grain size is 0.7μm, and the compressive strength at 600℃ exceeds 1000MPa.
[0062] Example 5
[0063] Step 1: prepare raw materials: using ammonium rhenate, lutetium nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the ratio of ammonium rhenate and lutetium nitrate so that the total volume of lutetium oxide generated by metal rhenium in ammonium rhenate and lutetium in lutetium nitrate is 100%, and the volume of lutetium oxide generated by lutetium in lutetium nitrate accounts for 10.0% of the total volume; the ratio of ammonium rhenate, ammonium nitrate and glycine is calculated according to a molar ratio of 1:2.5:5.4, and the ratio of stearic acid is calculated according to 0.2% of the mass of metal rhenium in ammonium rhenate.
[0064] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, volatilize and concentrate the solution to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 800°C to obtain a rhenium-coated nano-lutetium oxide core-shell alloy powder with a powder size of 35nm.
[0065] Step 3: Forming and sintering: After pressing and forming, the formed body is pre-sintered by spark plasma in vacuum, the pre-sintering temperature is 1670℃, the holding time is 1min, and then the temperature is lowered to the densification sintering temperature of 1450℃ and the holding time is 5min, and the nano-lutetium oxide coherent reinforced rhenium alloy can be prepared. The relative density is 98.9%, the average grain size is 0.7μm, and the compressive strength at 600℃ exceeds 1000MPa.
[0066] Example 6
[0067] Step 1: Prepare raw materials: take ammonium metatungstate, cerium nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the ratio of ammonium metatungstate and cerium nitrate, so that the total volume of cerium oxide generated by metal tungsten in ammonium metatungstate and cerium in cerium nitrate is 100%, and the volume of cerium oxide generated by cerium in cerium nitrate is 15.0%; the ratio of ammonium metatungstate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:1.5:3.2, and the amount of stearic acid is 0.2% of the mass of metal tungsten in ammonium metatungstate.
[0068] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, volatilize the solution, concentrate it to form a transparent and uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 750°C to obtain a tungsten-coated nano-cerium oxide core-shell alloy powder with a powder size of 27nm and a compressive strength of more than 1000MPa at 600°C.
[0069] Step 3: Molding and sintering: The tungsten-coated nano-cerium oxide core-shell alloy powder obtained in step 2 is pressed to form a formed body, and the formed body is pre-sintered by spark plasma in a vacuum at a pre-sintering temperature of 1600°C for 1 minute, and then cooled to a densification sintering temperature of 1400°C for 5 minutes to prepare a nano-cerium oxide coherent reinforced tungsten alloy.
[0070] The relative density of the obtained nano-cerium oxide coherent reinforced tungsten alloy is 99.7%, the average grain size is 0.5 μm, and the compression strength at 600° C. exceeds 1000 MPa.
[0071] Example 7
[0072] Step 1: Prepare raw materials: take ammonium metatungstate, hafnium nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the proportion of ammonium metatungstate and hafnium nitrate, so that the total volume of hafnium oxide generated from metal tungsten in ammonium metatungstate and hafnium in hafnium nitrate is 100%, and the volume of hafnium oxide generated from hafnium in hafnium nitrate is 15.0%; the proportion of ammonium metatungstate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:1.5:3.2, and the amount of stearic acid is 0.2% of the mass of metal tungsten in ammonium metatungstate.
[0073] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, volatilize and concentrate the solution to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 750°C to obtain a tungsten-coated nano-hafnium oxide core-shell alloy powder with a powder size of 27nm.
[0074] Step 3: Forming and sintering: The tungsten-coated nano-hafnium oxide core-shell alloy powder obtained in step 2 is pressed to form a formed body, and the formed body is pre-sintered by spark plasma in a vacuum at a pre-sintering temperature of 1600°C for 1 minute, and then cooled to a densification sintering temperature of 1400°C for 5 minutes to prepare a nano-hafnium oxide coherent reinforced tungsten alloy.
[0075] The relative density of the obtained nano-hafnium oxide coherent reinforced tungsten alloy is 99.7%, the average grain size is 0.5 μm, and the compressive strength at 600°C exceeds 1000 MPa.
[0076] Example 8
[0077] Step 1: Prepare raw materials: take ammonium metatungstate, thorium nitrate, ammonium nitrate, stearic acid and glycine as raw materials, calculate the proportion of ammonium metatungstate and thorium nitrate, so that the total volume of thorium oxide generated from the metal tungsten in the ammonium metatungstate and the thorium in the thorium nitrate is 100%, and the volume of thorium oxide generated from the thorium in the thorium nitrate is 15.0%; the proportion of ammonium metatungstate, ammonium nitrate and glycine is calculated according to the molar ratio of 1:1.5:3.2, and the amount of stearic acid is 0.2% of the mass of the metal tungsten in the ammonium metatungstate.
[0078] Step 2: prepare alloy powder: dissolve various raw materials in water to prepare a solution, heat the solution at 200°C, volatilize and concentrate the solution to form a transparent uniform gel, increase the temperature to 500°C to cause a combustion reaction to obtain a precursor powder; reduce the precursor powder in hydrogen at a reduction temperature of 750°C to obtain a tungsten-coated nano-thorium oxide core-shell alloy powder with a powder size of 27nm.
[0079] Step 3: Forming and sintering: The tungsten-coated nano-thorium oxide core-shell alloy powder obtained in step 2 is pressed to form a formed body, and the formed body is pre-sintered by spark plasma in a vacuum at a pre-sintering temperature of 1600°C for 1 minute, and then cooled to a densification sintering temperature of 1400°C for 5 minutes to prepare a nano-thorium oxide coherent reinforced tungsten alloy.
[0080] The relative density of the obtained nano-thorium oxide coherent reinforced tungsten alloy is 99.7%, the average grain size is 0.5 μm, and the compressive strength at 600°C exceeds 1000 MPa.
[0081] Comparative Example 1
[0082] The same method as in Example 1 was used except that the modifier stearic acid was not used.
[0083] Results Figure 3-4 .
[0084] By observing the alloy prepared by the present invention through transmission electron microscopy and high-resolution transmission, it can be observed that the oxide of the second phase high melting point metal is dispersed in the refractory metal, for example Figure 1 The TEM image of the alloy of Example 1 is shown, which shows the dispersed distribution of aluminum oxide in the tungsten matrix. It can also be observed that the oxide of the second phase high melting point metal forms a coherent phase interface with the refractory metal, for example Figure 2 is a HRTEM photograph of the nano-alumina coherent reinforced tungsten alloy prepared in Example 1 of the present invention, showing the coherent interface formed by the alumina and the tungsten matrix; Figure 3 This is a TEM picture of an alumina reinforced tungsten alloy prepared without using the method provided by the present invention, and the second phase particles appear as huge agglomerates. Figure 4 This is a HRTEM photo of an aluminum oxide reinforced tungsten alloy that is not prepared using the method provided by the present invention. It is difficult for the two to form a coherent interface;
[0085] It is explained that the method of the present invention can obtain a phase boundary coherent refractory alloy, in which the oxide of the second phase high melting point metal forms a coherent phase interface with the refractory metal, and the oxide of the second phase high melting point metal is dispersed in the refractory metal.
[0086] The present invention proves the feasibility of the method of the present invention through multiple embodiments. At the same time, as long as the second phase high melting point metal can generate oxides at 500°C to 800°C and maintain the oxide form at 600°C to 1200°C under hydrogen conditions without decomposing into metal elements, it can be used in the present invention, such as one of lutetium, cerium, hafnium, thorium, and lanthanum.
[0087] The product prepared by the method of the present invention can be used as a turbine blade and combustion chamber material that needs to be resistant to high temperatures and have excellent mechanical properties.
[0088] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A phase boundary coherent refractory alloy, characterized in that: The oxide of the second phase high melting point metal in the phase boundary coherent refractory alloy forms a coherent phase interface with the refractory metal, and the oxide of the second phase high melting point metal is dispersed in the refractory metal; The refractory metal is selected from one of tungsten, molybdenum or rhenium; the second phase high melting point metal is selected from one of zirconium, yttrium, aluminum, lutetium, cerium, hafnium, thorium and lanthanum; The volume fraction of the oxide of the second phase high melting point metal in the phase boundary coherent refractory alloy is 3%-30%.
2. The phase boundary coherent refractory alloy according to claim 1, characterized in that: The relative density of the phase boundary coherent refractory alloy is not less than 98.0%, and the grain size is less than 1.0 μm.
3. A method for preparing a phase boundary coherent refractory alloy, characterized in that: The phase boundary coherent refractory alloy is the phase boundary coherent refractory alloy according to claim 1 or 2, and the preparation method thereof comprises the following steps: Step 1, preparing raw materials: using a water-soluble salt of a refractory metal, a water-soluble salt of a second-phase high-melting-point metal, a modifier, ammonium nitrate and glycine as raw materials; wherein the ratio of the water-soluble salt of the refractory metal to the water-soluble salt of the second-phase high-melting-point metal is such that, based on the sum of the volume of the refractory metal in the water-soluble salt of the refractory metal and the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal being 100%, the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal is 3%-30%; the refractory metal is selected from one of tungsten, molybdenum or rhenium; the second-phase high-melting-point metal is selected from one of zirconium, yttrium, aluminum, lutetium, cerium, hafnium, thorium and lanthanum; the modifier is a water-soluble small molecule compound or a polymer; Step 2, preparing alloy powder: mixing the raw materials and preparing a uniform aqueous solution, and in-situ compounding under heating conditions to form a core-shell complex gel; then heating to 500°C to 700°C to produce a combustion reaction to prepare a coated core-shell precursor powder containing a refractory metal oxide and a second phase high melting point metal oxide; continuing to reduce the coated core-shell precursor powder in a reducing gas at a temperature of 600°C to 1200°C to prepare an alloy powder with a core-shell structure in which a refractory metal is coated with a second phase high melting point metal oxide; Step 3, forming and sintering: the alloy powder obtained in step 2 is pressed and formed, and a two-step sintering method of spark plasma is adopted, firstly, the temperature is raised to the pre-sintering temperature by spark plasma sintering method, and the temperature is kept for 1min to 2min, then the temperature is reduced to the densification sintering temperature, and the temperature is kept for 3min to 6min, so as to obtain a phase boundary coherent refractory alloy; wherein the pre-sintering temperature is 1500℃ to 1800℃, and the densification sintering temperature is 120℃ to 350℃ lower than the pre-sintering temperature.
4. The preparation method according to claim 3, characterized in that In step 1, the water-soluble salt of the refractory metal is selected from ammonium metatungstate, sodium tungstate, ammonium tungstate, ammonium molybdate, sodium molybdate, potassium molybdate, ammonium rhenate, sodium rhenate, and potassium rhenate; In step 1, the water-soluble salt of the second phase high melting point metal is selected from aluminum nitrate, zirconium nitrate, yttrium nitrate, lutetium nitrate, cerium nitrate, hafnium nitrate, thorium nitrate, lanthanum nitrate, zirconium chloride, yttrium chloride, aluminum chloride, lutetium chloride, cerium chloride, hafnium chloride, thorium chloride, and lanthanum chloride.
5. The preparation method according to claim 3, characterized in that: In step 1, based on the sum of the volume of the refractory metal in the water-soluble salt of the refractory metal and the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal being 100%, the volume of the corresponding oxide generated by the second-phase high-melting-point metal in the water-soluble salt of the second-phase high-melting-point metal is 5.0% to 15.0%.
6. The preparation method according to claim 3, characterized in that: In step 1, the modifier is selected from one of stearic acid, polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, and sodium dodecyl sulfate; The amount of the modifier added is 0.1% to 0.5% of the mass of the refractory metal in the water-soluble salt of the refractory metal; The molar ratio of the water-soluble salt of the refractory metal, ammonium nitrate and glycine is 1:1.3-2.6:3-6.
7. The preparation method according to claim 3, characterized in that: In step 2, the temperature used for in-situ composite formation of core-shell complex gel under heating conditions is 150° C. to 300° C.; In step 2, the solvent in the aqueous solution is evaporated and concentrated under heating conditions to obtain an in-situ composite core-shell complex gel.
8. The preparation method according to claim 3, characterized in that: In step 2, the temperature of the combustion reaction is 500°C-650°C; the temperature range of the reduction is 700°C-800°C.
9. The preparation method according to claim 3, characterized in that: In step 3, the pre-sintering temperature is 1550°C to 1650°C, and the holding time is 1min to 2min; In step 3, the densification sintering temperature is 150° C. to 300° C. lower than the pre-sintering temperature, and is kept warm for 4 to 5 minutes.
10. An application of a phase boundary coherent refractory alloy, characterized in that: Application of the phase boundary coherent refractory alloy described in any one of claims 1-2 as turbine blade and combustion chamber material.
Citation Information
Patent Citations
Preparation method for rare earth oxide doped tungsten powder
CN102626785A
Method for manufacturing high-dispersion ultrafine molybdenum-based powder
CN103008676A
Preparation method of high-density fine-grain tungsten-based material
CN109457159A
Method for preparing high-density ultrafine-grained rare earth oxide doped tungsten alloy
CN110560700A
High-hardness composite oxide dispersion strengthened ODS tungsten alloy and preparation method thereof
CN112011703A